Migration matters: How migration is critical to contemporary human–environment geography. Issue 8 (25th July 2019) - Jokisch, Brad D.; Radel, Claudia; Carte, Lindsey; Schmook, Birgit
Abstract: Human migration plays a critical role in numerous contemporary environmental concerns including global climate change and environmental justice. This review characterizes the ways migration is critical to contemporary human–environment geography. We delineate four themes from the literature based on (a) how migration affects the environment; (b) how the environment and/or environmental events affect migration; (c) how migration produces uneven environmental benefits and burdens; and (d) how environmental displacement/dispossession produces migration and vice versa. We articulate five recommendations for a research agenda that integrates migration processes, recognizes migration as a heterogeneous process, and approaches human–environment interactions holistically and non‐deterministically.